Exploring the reasons for theory-practice gap in emergency nursing education: A qualitative research - Shima Safazadeh; Alireza Irajpour; Nasrollah Alimohammadi; Fariba Haghani (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Nursing is a scientific profession, based on theory and art of care. However, the theory-practice gap has become the biggest challenge of this profession and decreases the quality of service both in teaching and practice. Thus, it seems necessary to search for these reasons in situations such as emergency department - which has an effective role in patients' health. OBJECTIVES: The objectives of this study were to find the perceived reasons for the theory-practice gap in the process of emergency nursing education from the perspective of professors, nurses, and students, as well as doctors, since they cooperate with nurses and students in the training environment. METHODS: A qualitative study was carried out; this included 18 deep, semi-structured interviews in 7 months with the people involved in the process of emergency department apprenticeship alongside with observing the activities of stakeholders. The data analysis was done in accordance with content analysis method including three steps of preparation, organization, and reporting. RESULTS: The perceived reasons for theory-practice gap were classified into 13 secondary categories. At the end of data analysis, five main categories of student, instructor, environment, culture, and the organizational process, and finally, two themes of "input" and "process" emerged. CONCLUSIONS: Nursing students in emergency department face a number of challenges in implementing theory into practice which stems from the faculty as an academic environment and the hospital as an educational environment. These underpinning reasons for the theory-practice gap influence the quality of nursing education and care delivery in emergency department. Hence, decreasing the theory-practice gap lies in the amendment of any of these factors.